1 & 2 Thessalonians: an introduction and study guide : encountering the Christ group at Thessalonike - Ascough, Richard S. (T & T Clark study guides to the New Testament, 2020)
Preface -- 1. Founding a Christ Group at Thessalonike -- 2. Written Communication: 1 Thessalonians -- 3. Affirming Relationships -- 4. Standing Firm in Troubling Times -- 5. Writing with Authority: 2 Thessalonians -- 6. Adjusting for New Circumstances -- Index.